Pengaruh Serbuk Besi Dan Natrium Silika Serta Natrium Hidroksida Terhadap Beton - Yosua Kevin Jordan Randa; Frans Phengkarsa; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The use of iron filings as a partial substitute for sand in concrete mixes is an alternative to reduce iron filings waste which can pollute the environment. This study used iron powder and sodium silica and sodium hydroxide in the concrete mixture which aims to determine the effect of the mechanical properties of the resulting concrete. In this study, a series of process stages were carried out which included testing material characteristics and then planning the composition of the concrete mix withmix design as well as making test specimens in the form of cylinders with a size of 15 cm x 30 cm as many as 48 test objects and blocks with a size of 60 cm x 15 cm x 15 cm as many as 12 test objects then testing the test objects with a predetermined concrete age of 7 days, 21 days , and 28 days.From the results of the study using iron filings with variations of 0%, 10%, 15%, 20%, the compressive strength values ​​were 25.146 MPa, 18.514 MPa, 17.505 MPa and 16.770 MPa, while the tensile strength values ​​obtained were 2.642 MPa, 1.463 MPa , 1.415 MPa, 1.345 MPa and the flexural strength values ​​obtained were 2.642 MPa, 1.463 MPa, 1.415 MPa and 1.345 MPa respectively. The results above show that the use of iron powder and sodium silica and sodium hydroxide can reduce the mechanical properties of concrete.